Normalization of NAD+ Redox Balance as a Therapy for Heart Failure. Issue 12 (20th September 2016) - Lee, Chi Fung; Chavez, Juan D.; Garcia-Menendez, Lorena; Choi, Yongseon; Roe, Nathan D.; Chiao, Ying Ann; Edgar, John S.; Goo, Young Ah; Goodlett, David R.; Bruce, James E.; Tian, Rong
Abstract : Background: Impairments of mitochondrial function in the heart are linked intricately to the development of heart failure, but there is no therapy for mitochondrial dysfunction. Methods: We assessed the reduced/oxidized ratio of nicotinamide adenine dinucleotide (NADH/NAD + ratio) and protein acetylation in the failing heart. Proteome and acetylome analyses were followed by docking calculation, mutagenesis, and mitochondrial calcium uptake assays to determine the functional role of specific acetylation sites. The therapeutic effects of normalizing mitochondrial protein acetylation by expanding the NAD + pool also were tested. Results: Increased NADH/NAD + and protein hyperacetylation, previously observed in genetic models of defective mitochondrial function, also are present in human failing hearts as well as in mouse hearts with pathologic hypertrophy. Elevation of NAD + levels by stimulating the NAD + salvage pathway suppressed mitochondrial protein hyperacetylation and cardiac hypertrophy, and improved cardiac function in responses to stresses. Acetylome analysis identified a subpopulation of mitochondrial proteins that was sensitive to changes in the NADH/NAD + ratio. Hyperacetylation of mitochondrial malate-aspartate shuttle proteins impaired the transport and oxidation of cytosolic NADH in the mitochondria, resulting in altered cytosolic redox state and energy deficiency. Furthermore, acetylation of oligomycin-sensitive conferring protein at lysine-70 in adenosine triphosphate synthase complex promoted its interaction with cyclophilin D, and sensitized the opening of mitochondrial permeability transition pore. Both could be alleviated by normalizing the NAD + redox balance either genetically or pharmacologically. Conclusions: We show that mitochondrial protein hyperacetylation due to NAD + redox imbalance contributes to the pathologic remodeling of the heart via 2 distinct mechanisms. Our preclinical data demonstrate a clear benefit of normalizing NADH/NAD + imbalance in the failing hearts. These findings have a high translational potential as the pharmacologic strategy of increasing NAD + precursors are feasible in humans. Abstract : Supplemental Digital Content is available in the text.